The effects of intermittent exposure to hypoxia during endurance exercise training on the ventilatory responses to hypoxia and hypercapnia in humans - Katayama, K.; Sato, Y.; Ishida, K.; Mori, S.; Miyamura, M. (European Journal of Applied Physiology, 1998)
The present study was performed to investigate the effects of a combination of intermittent exposure to hypoxia during exercise training for short periods on ventilatory responses to hypoxia and hypercapnia (HVR and HCVR respectively) in humans. In a hypobaric chamber at a simulated altitude of 4,500 m (barometric pressure 432 mmHg), seven subjects (training group) performed exercise training for 6 consecutive days (30 min a day)1), while six subjects (control group) were inactive during the same period. The HVR, HCVR and maximal oxygen uptake (VO2 max) for each subject were measured at sea level before (pre) and after exposure to intermittent hypoxia. The post exposure test was carried out twice, i.e. on the 1st day and 1 week post exposure. It was found that HVR, as an index of peripheral chemosensitivity to hypoxia, was increased significantly (P < 0.05) in the control group after intermittent exposure to hypoxia. In contrast, there was no significant increase in HVR in the training group after exposure. The HCVR in both groups was not changed by intermittent exposure to hypoxia, while VO2max increased significantly in the training group.These results would suggest that endurance training during intermittent exposure to hypoxia depresses the increment of chemosensitivity to hypoxia, and that intermittent exposure to hypoxia in the presence or absence of exercise training does not induce an increase in the chemosensitivity to hypercapnia in humans.